2020
DOI: 10.1155/2020/7586154
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Traffic Flow Forecasting Method Based on RNN-GCN and BRB

Abstract: As an important part of a smart city, intelligent transport can effectively reduce energy consumption and environmental pollution. Traffic flow forecasting provides a reliable traffic dispatch basis for intelligent transport, and most of the existing prediction methods only predict a single saturation or speed and do not use the saturation and speed in a unified way. This paper proposes a new traffic flow prediction method based on RNN-GCN and BRB. First, the belief rule base (BRB) is used for data fusion to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…It can only handle Euclidean data since its translation invariance. RNN [30], LSTM, and GRU are suitable for processing timeseries data [31][32][33]. These networks rely on the sequential temporal order of the data itself.…”
Section: B Deep Learning Methodsmentioning
confidence: 99%
“…It can only handle Euclidean data since its translation invariance. RNN [30], LSTM, and GRU are suitable for processing timeseries data [31][32][33]. These networks rely on the sequential temporal order of the data itself.…”
Section: B Deep Learning Methodsmentioning
confidence: 99%
“…Tis model uses external factors as dynamic attributes and static attributes and designs an attribute-augmented unit to encode and integrate those factors into the spatiotemporal graph convolution model and perform trafc speed prediction. In another approach, Zhu et al [104] proposed BRBbased RNN-GCN model for trafc fow prediction, which solves the existing issues of trafc fow prediction models such as saturation or speed. In the scenarios related to trafc prediction, how to solve the spatiotemporal dependence is an important research direction.…”
Section: Gcn For Computer Visionmentioning
confidence: 99%
“…A dataset provided by the University of Minnesota Duluth Data center was utilized to demonstrate the effectiveness of the proposed methods, and the results have indicated that the proposed method outperforms the auto-regressive integrated moving average and wavelet neural network in terms of prediction accuracy. Zhu et al [ 39 ] integrated the GNN with RNN to extract the spatial and temporal correlations of traffic data. The belief rule-based algorithm was adopted for data fusion, and the fused traffic data were fed into the proposed methodology for traffic flow prediction.…”
Section: Literature Reviewmentioning
confidence: 99%